Physico-chemical, antioxidant and sensory properties of stirred yoghurt containing Ber (Zizyphus mauritiana) fruit extract - ., Preeti; Poonia, Amrita (Indian Journal of Dairy Science, 2021)
In this study Ber polyphenol extract (BPE) was prepared by vacuum evaporation of ethanol extract of edible portion (pulp and skin) and fortified into stirred yoghurt. A ratio of 0.20 BPE (mg/g) to 1.0 BPE (mg/g) was added for yoghurt preparation. Based on various sensory attributes, stirred yoghurt with BPE 0.8 mg /g per cent was chosen as best among these samples when compared with the control stirred yoghurt. Optimized yoghurt with 0.8 mg/g BPE contains 82.36±0.545 % moisture, 6.45±0.08 % protein, 0.98±0.001 % ash, 0.1% fat, 0.026 ppm Mn, 3.85 ppm Zn, 0.9407 ppm Cu and 950 ppm Ca, respectively. Water holding capacity of the fortified yoghurt increased significantly on increasing the BPE concentration from 41.23±0.73g/100g to 46.66 ± 1.13g/100g. Total phenolic content increased significantly on increasing the concentration of BPE 0.8 mg/g. Fortification of BPE resulted in TPC of 504.4± 9.3μg GAE/ g from 216.88±9.41μg GAE/ g in control sample. Storage period of 20 days showed non-significant losses in total phenolic content and antioxidant capacity. TPC decreased from 504.4±9.3 μg GAE/g to 438.17±15.58 μg GAE/g and % DPPH inhibition decreased from 74.22 ±2.77% to 67.4 ±1.32% after 20 days storage at 4°C.